ANALISIS EFISIENSI PEMASARAN PRODUK AGROINDUSTRI PERIKANAN (Studi Kasus Pemasaran Ikan Teri di Desa Meunasah Keudee Kabupaten Aceh Besar) - Evi Lisna; Sofyan Sofyan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
Efficiency Analysis of Marketing in Fisheries Agro-industry(A Case Study: Marketing of Dried Anchovy in Meunasah Keudee village,District of Aceh Besar)ABSTRACT. The issue of marketing efficiency is still an important topic to be discussed in agribusiness. The specific goals of this research are: (1) identifying marketing channel of dried anchovy and (2) analyzing market performance of dried anchovy (includes margin, profit margin, share as well as value chain). This research is quantitative and qualitative researches using observations, in-depth interviews and questionnaires. Field research was conducted in Meunasah Keudee Village, Aceh Besar District, Aceh Province. This location is selected from areas that are most popular as a central production of dried Anchovy in Aceh. Results from this research indicated that the marketing margin in all channels was enormous and unwell distributed yet. Increasing marketing efficiency at market level in local market through reducing marketing cost (transportation, handling, packing and loss) is important. Similarly, encouragement of investment in those efficiency activities are still essential.